Synthesis and Characterization of New D-π-D Type Schiff Base Ligands - Karaoglan, G. Keser; Erden, I.; Avciata, U. (POLISH CHEMICAL SOC, 2009)
Two new Schiff bases with D-pi-D type have been successfully synthesized using the reaction of 3,3'-dimethylnapthide and 3,3',5,5'-tetramethylbenzidine with 4-(dimethylamino)cinnamaldehyde. The Schiff base ligands L-1 and L-2 have been characterized by IR, UV-visible, H-1 NMR and fluorescence spectra, as well as TGA-DSC-DTG, elemental analyses and mass spectra.
Keywords: Schiff base; D-pi-D; fluorescence; COMPLEXES; NICKEL(II); DERIVATIVES; COBALT(II); EMITTERS; CRYSTAL; Chemistry